V. 1 - "Shah, Giri Raj" (New Delhi, 1998)
Encyclopaedia of Narcotic Drugs And Psychotropic Substances (3 Vols.) The book presents each and every of drug abuse and drug trafficking, evils. measures taken by the governments and NGOs to eradicate it and the progress.
Keywords: Drug abuse - Encyclopedias